2008
DOI: 10.1007/978-3-540-85485-2_14
|View full text |Cite
|
Sign up to set email alerts
|

SORMA – Business Cases for an Open Grid Market: Concept and Implementation

Abstract: Abstract. Economic mechanisms enhance technological solutions by setting the right incentives to reveal information about demand and supply accurately. Market or pricing mechanisms are ones that foster information exchange and can therefore attain efficient allocation. By assigning a value (also called utility) to their service requests, users can reveal their relative urgency or costs to the service. The implementation of theoretical sound models induce further complex challenges. The EU-funded project SORMA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…In formula (6), it can be ensured that a random integer between 0 and 1 can appear in the crossover process, and there is at least one component coming from , …”
Section: Differential Genetic Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…In formula (6), it can be ensured that a random integer between 0 and 1 can appear in the crossover process, and there is at least one component coming from , …”
Section: Differential Genetic Algorithmmentioning
confidence: 99%
“…The simulation experiment has shown that resource utilization rate has been improved. In Literature [6][7], a random integer programming is proposed to optimize resources, and make dynamic allocation of resources by examining resource overhead of various stages. In Literature [8], genetic algorithm, basic ant colony algorithm and resource scheduling algorithm are proposed to allocate cloud computing resources for users reasonably with the target of the completion time of the best overall task.…”
Section: Introductionmentioning
confidence: 99%
“…Several market-based allocation systems for grids, such as Sorma [22] and Nimrod/G [13], use bargaining or negotiation to determine the resource price. The advantage of this approach is that sellers and buyers communicate directly, without a third party mediating an allocation.…”
Section: Related Workmentioning
confidence: 99%
“…Several market-based allocation systems for grids, such as Sorma [16] and Nimrod/G [3], use bargaining or negotiation to determine the resource price. The advantage of this approach is that sellers and buyers communicate directly, without a third party mediating an allocation.…”
Section: Related Workmentioning
confidence: 99%